IMPROVING STUDENTS' LISTENING-RESPONSE SKILL - Muhammad Rifqi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2007)
Responding to questions is an important skill to develop. Sometimes students cannot give suitable responses to some specific questions. In order to be able to give suitable response to a question students have to understand what a given question expects. Failing to anticipate what the question asks will lead the students to give unsuitable response. Giving feedback to the students in anticipating what a question asks is believed to be able to improve their abilities to respond to the questions appropriately.I conducted classroom research on the teacher's feedback to improve the students' question-response skill in my listening class in EFL setting. Sixty-nine participants were the fourth-semester students taking Listening IV in 2005. They were asked to listen to and answer the recorded oral questions taken from a standardized model test. The test results were evaluated and the researcher gave feedback to the students by giving the key and discussing the case specific to each question item. After giving teacherâ€™s feedback, the participants were asked to listen and respond to a number of questions and the result, again, were evaluated. This cycles were iterated for 3 times. The teacher's feedback comprises sound recognition, guessing the word's or phrase's  meaning, and grammar.The research findings showed significant improvement on the students' question-response skill indicated by the increased mean score especially after implementing the third cycle.